Pengembangan Soal High Order Thinking Skill (HOTS) pada Pembelajaran Tematik Kelas V di SDN 36 Pontianak Selatan - Safitri, Dwi Ajeng; Kartono, Kartono; Pranata, Rio (AS-SABIQUN, 2024)
The research carried out aims to develop questions in learning activities in the form of High Order Thinking Skill (HOTS) questions created for class V learning at SDN 36 South Pontianak which meet the requirements to help evaluate learning activities in the 2013 curriculum. This research method is a method RnD with the model namely ADDIE. This research data was obtained by involving 2 classes with the first class having 10 students and the second class having 20 students with a total of 30 class V students at the South Pontianak 36 State Elementary School, 1 material and language expert validator, 1 construct expert validator. The techniques for collecting data in this research are interviews and questionnaires. The results after the research show that the process of developing High Order Thinking Skill HOTS questions in thematic learning activities in class V Elementary School has gone through 4 stages of the ADDIE model research from the 5 stages. The HOTS question product validity activity resulted in very feasible criteria with an average score of 95% for the material and language aspects and 96% with very feasible criteria for the construct aspect. After carrying out validity tests, reliability tests, differential power analysis, and item difficulty level tests, the results obtained were 50 questions developed which had high reliability with an average of 0.897, good item differential power with an average of 0.377, and medium difficulty level test with an average of 0.585. So it can be said that the questions developed are appropriate and have been declared to meet the HOTS characteristics.